Analisis Kualitas Layanan Berdasarkan Persepsi Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Manado - sekin, wayan (Universitas Sam Ratulangi, 2018)
Gap analysis shows that the gap with the lowest value on the assurance dimension, then following by realibility and emphaty. overall as ingle measure of service quality or serqual gap from the Manado pratama tax office, based onÂ respondent perception is positive number.Keywords: servqual, service quality, realiability, emphaty